The Potentials and Challenges of Achieving Sustainability through Charcoal Producer Associations in Kenya: A Missed Opportunity? - Kamwilu, E.; Duguma, L.A.; Orero, L. (MDPI, 2021)
The charcoal industry, specifically charcoal production, is tremendously valuable to Kenya for its contribution to economic, social and environmental nexus. Considering the degradation of ecosystems and charcoal production’s critical role, the government established the Forest (charcoal) rules of 2009, assigning commercial charcoal production under Charcoal Producer Associations (CPAs). Identifying numerous bans in the recent past, this paper sets out to understand CPAs’ potentials and challenges in attaining sustainability within the sector. Using focus group discussions with CPA members from Tana River and Kitui counties, the paper outlines analysed data within the functionality, governance and policy implications parameters of operation. The findings show high economic value for the members and an in-depth environmental significance to the communities within which these CPAs exist. Thus, we propose a schematic to enhance charcoal production processes to achieve sustainable ecosystems and livelihoods. There is high potential within the CPAs for the sector’s sustainability through monitoring platforms, restoration plans, adopting sustainable practices, knowledge dissemination and societal advancement. To advance this untapped potential of these associations, we recommend building their technical, business and governance skills, exploring various restoration schemes, financial and regulatory support in implementation, and policy support.